Necesidad de incorporar una sección en el capítulo xa (x 1) de la legislación penal ecuatoriana, normas que sancionen la apropiación indebida de los recursos de biodiversidad. - Merchán Palacios, Sucety Jhuliana (2010)
It constitutes a prerequisite for qualifying as a lawyer conducting legal research to identify potential measures of solution to the problem of social reality. I have seen fit to do my research work considering the relevance of the topic and the contribution and give to the local, regional and national levels concerning the environment and its importance for humans. With the evolution of global society have increased the behaviors that violate legal rights protected by the rule, and most have also been recognized human rights to help raise the quality of life and improve standards of social coexistence. In our country the constitutional standard has mainly evolved significantly in recent years, this due to a greater democratization of decision making, even with flaws, allowed to discuss and approve oriented constitutional recognition of rights, principles and guarantees. Continuous innovation in terms of fundamental rights has allowed the Constitution of 2008, prepared on the basis of the wider democratic discussion by all social sectors in Ecuador, to recognize for the first time in the history or rights to nature Pacha Mama. This has provided a clear example to the world of the need to protect biodiversity through the constitutional provision. My thesis is developed first from a broad overview, analyzing the causes of an economic system that has caused unrest and destruction throughout the planet earth, the result of this is that ostensibly has increased pollution levels in the atmosphere producing global warming that has caused destruction resulting in the land. Second moment, my analysis aims to recover the importance of our country's biodiversity resources, to be considered a privileged area by the large presence of species of flora and fauna that exist in other places not therefore stress the need to provide protection to these resources through the criminal standard, which allows enforcement function decreased as biopiracy practices that infringe on our resources. I also thought, it important to make a critical legal study both constitutional rules as ordinary in order to establish the supremacy of the Constitution and the need for lower-level standards are geared to develop accurately the sovereign mandate of the Ecuadorian people, and we must protect our biodiversity resources by preventing and punishing the criminal standard the commission of conduct that adversely affects the legal rights protected. Biopiracy is a modern behavior that has a primary objective the seizure of biodiversity resource, ancestral knowledge and genetic material in these resourcerich regions. This activity is performed mainly for commercial purposes, through which transnational companies using patents as a working tool seize the natural resources of Latin American peoples and especially of ours to be produced and marketed worldwide. The field research allowed me to establish the need for a reform of the Ecuadorian Criminal Code to protect biodiversity resources and impose a penalty of imprisonment to those engaged in biopiracy in the country.